Are members of mutual aid groups better equipped for addiction recovery? European cross-sectional study into recovery capital, social networks, and commitment to sobriety. (3rd September 2021) - Martinelli, Thomas F.; van de Mheen, Dike; Best, David; Vanderplasschen, Wouter; Nagelhout, Gera E.
Abstract: An increasing body of evidence shows that informal mutual aid groups benefit those in addiction recovery. However, attention for mutual aid groups in practice and policy varies internationally and is only recently emerging in continental Europe. Existing evidence is mostly limited to studies of Alcoholics Anonymous groups in the United States. The aim of this cross-sectional study is to examine the relationship between membership of a variety of mutual aid groups and recovery capital, participation in social networks, and commitment to sobriety for individuals in drug addiction recovery ( N = 367), living in the UK, the Netherlands, and Belgium. A convenience sample of participants completed an extensive assessment about their recovery experiences. Sixty-nine percent of participants reported lifetime (ever) membership of different mutual aid groups. Analyses reveal that membership of mutual aid groups is strongly associated with more participation and (self-reported) changes in social networks, greater levels of recovery capital, and a stronger commitment to sobriety. The findings suggest that participation in mutual aid groups may support addiction recovery through multiple mechanisms of change in favor of recovery. These findings highlight how mutual aid support may complement formal addiction treatment.